Systemic administration of the antisense oligonucleotide NS‐089/NCNP‐02 for skipping of exon 44 in patients with Duchenne muscular dystrophy: Study protocol for a phase I/II clinical trial - Takami Ishizuka; Hirofumi Komaki; Yasuko Asahina; Harumasa Nakamura; Norio Motohashi; Eri Takeshita; Yuko Shimizu‐Motohashi; Akihiko Ishiyama; Chihiro Yonee; Shinsuke Maruyama; Eisuke Hida; Yoshitsugu Aoki (Wiley, 2023)
Abstract Aim The purpose of this study is to evaluate the safety and pharmacokinetics of the novel morpholino oligomer NS‐089/NCNP‐02 which can induce exon 44 skipping, in patients with DMD. Additionally, we aimed to identify markers predictive of therapeutic efficacy and determine the optimal dosing for future studies. Methods This is an open‐label, dose‐escalation, two‐center phase I/II trial in ambulant patients with DMD, presence of an out‐of‐frame deletion, and a mutation amenable to exon 44 skipping. Part 1 is a stepwise dose‐finding stage (4 weeks) during which NS‐089/NCNP‐02 will be administered intravenously at four dose levels once weekly (1.62, 10, 40, and 80 mg/kg); Part 2 is a 24‐week evaluation period based on the dosages determined during Part 1. The primary (safety) endpoints are the results of physical examinations, vital signs, 12‐lead electrocardiogram and echocardiography tests, and adverse event reporting. Secondary endpoints include expression of dystrophin protein, motor function assessment, exon 44 skipping efficiency, plasma and urinary NS‐089/NCNP‐02 concentrations, and changes in blood creatine kinase levels. Discussion Exon‐skipping therapy using ASOs shows promise in selected patients, and this first‐in‐human study is expected to provide critical information for subsequent clinical development of NS‐089/NCNP‐02.